1979
DOI: 10.1063/1.437584
|View full text |Cite
|
Sign up to set email alerts
|

Molecular theory of translational diffusion: Microscopic generalization of the normal velocity boundary condition

Abstract: A simple molecular theory is presented for the diffusion constant D for a test hard sphere translating in a hard sphere solvent. It is argued that there is a breakdown of the applicability of hydrodynamics in the neighborhood of the test particle due to collisional effects. It is shown that, as a consequence, the traditional hydrodynamic boundary condition (BC) on the particle–solvent normal relative velocity is incorrect for molecular motion. An approximate replacement for this BC is constructed from collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 31 publications
4
54
2
Order By: Relevance
“…In fact, the general result (27): (i) has a form which recalls the result obtained by Hynes et al [15] (by a quite different method and in the special case of the hard-sphere interaction model) for particles moving in a gas under ''slip'' boundary conditions, and (ii) explicitly expresses the simple dependence of D both on k R and on k S . It must be noted, however, that, while for D (and for the l.h.-ion mobility K) the contributions due to the Stokes' force and to the single collisions are only additive (and therefore separable), for the mean energy hi 1 this does not happen.…”
Section: Discussionsupporting
confidence: 69%
“…In fact, the general result (27): (i) has a form which recalls the result obtained by Hynes et al [15] (by a quite different method and in the special case of the hard-sphere interaction model) for particles moving in a gas under ''slip'' boundary conditions, and (ii) explicitly expresses the simple dependence of D both on k R and on k S . It must be noted, however, that, while for D (and for the l.h.-ion mobility K) the contributions due to the Stokes' force and to the single collisions are only additive (and therefore separable), for the mean energy hi 1 this does not happen.…”
Section: Discussionsupporting
confidence: 69%
“…First we analytically examine the contribution of each mode (binary, density and current) to the total friction/diffusion in the limit of large solute size. This analysis shows that the final expression for the zero frequency friction reduces to a form similar to that given by Hynes et al [18] and Mehaffey and Cukier [17]. The contribution from the density mode becomes zero as the microscopic structure of the solvent becomes unimportant to a large solute.…”
Section: Introductionsupporting
confidence: 61%
“…It was analytically shown by Gaskell and coworkers [13], that once the current mode makes the dominant contribution to diffusion the SE relation with the slip boundary condition can be recovered. Other theories, such as renormalized kinetic theory (ring theory) [14][15][16], repeated ring theory [17] and a semi-phenomenological theory by Hynes et al [18] have also demonstrated this cross-over to the hydrodynamics for large solutes.…”
Section: Introductionmentioning
confidence: 88%
“…For a heavy sphere with diffusing boundaries (which randomly scatter colliding particles according to the Maxwell-Boltzmann law) the translational Enskog friction is given by ξ e = 2 3 √ 2πmk B T γD 2 (1 + 2χ)/(1 + χ), where χ = 2/5 is the gyration ratio. It has been confirmed [25,26,[31][32][33] that the two sources of friction act in parallel, i.e. that the total friction ξ is given by…”
Section: B Determination Of the Frictionmentioning
confidence: 91%